2020
DOI: 10.1002/ange.202001436
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of High χ–Low N Diblock Copolymers by Polymerization‐Induced Self‐Assembly

Abstract: Polymerization-induced self-assembly (PISA) enables the scalable synthesis of functional block copolymer nanoparticles with various morphologies. Herein we exploit this versatile technique to produce so-called "high c-low N" diblock copolymers that undergo nanoscale phase separation in the solid state to produce sub-10 nm surface features. By varying the degree of polymerization of the stabilizer and coreforming blocks, PISA provides rapid access to a wide range of diblock copolymers, and enables fundamental t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…After the PSM blocks were converted into PGM blocks, a decrease in the solubility triggered the formation of multimolecular micelles with uniform sizes, as evidenced by the increasing D (Figures S2.3.3–S2.3.5) and the micelles observed in the spin-coated films (Figures S2.3.7–S2.3.8), similar to previous studies . It has been reported that for high-χ linear BCPs, micellization in selective solvents can aid in producing long-range-ordered morphologies in the solid state after solvent evaporation . However, for high-χ BBCPs, even with micellization in solution, we found it more difficult to achieve well-ordered morphologies in the solid state after solvent evaporation, which we attribute to a reduced mobility of BBCPs in comparison to linear BCPs.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…After the PSM blocks were converted into PGM blocks, a decrease in the solubility triggered the formation of multimolecular micelles with uniform sizes, as evidenced by the increasing D (Figures S2.3.3–S2.3.5) and the micelles observed in the spin-coated films (Figures S2.3.7–S2.3.8), similar to previous studies . It has been reported that for high-χ linear BCPs, micellization in selective solvents can aid in producing long-range-ordered morphologies in the solid state after solvent evaporation . However, for high-χ BBCPs, even with micellization in solution, we found it more difficult to achieve well-ordered morphologies in the solid state after solvent evaporation, which we attribute to a reduced mobility of BBCPs in comparison to linear BCPs.…”
Section: Resultssupporting
confidence: 88%
“…70 It has been reported that for high-χ linear BCPs, micellization in selective solvents can aid in producing long-range-ordered morphologies in the solid state after solvent evaporation. 55 However, for high-χ BBCPs, even with micellization in solution, we found it more difficult to achieve well-ordered morphologies in the solid state after solvent evaporation, which we attribute to a reduced mobility of BBCPs in comparison to linear BCPs.…”
Section: 1)mentioning
confidence: 65%
See 1 more Smart Citation
“…Another post-PISA method utilizes the advantages of RAFT-PISA (i.e., efficient polymer synthesis) for the subsequent preparation of various bulk morphologies. 169 These bulk morphologies are obtained directly from post-PISA polymer isolation. Finally, the preparation of composite nanomaterials also introduces interesting new possibilities.…”
Section: Conclusion/perspectivementioning
confidence: 99%
“…Recently, Armes and co-workers described a robust methodology that may prove useful for future sub-10 nm scaling research. 148 The authors reported the benefits of using polymerization induced self-assembly (PISA) 149 for the preparation of high χ-low N BCPs. The nanoparticle formed by the BCPs chains during the PISA process allow a preorganization at the molecular scale leading to rapid self-assembly unlike molecularly dissolved polymer chains.…”
Section: Discussionmentioning
confidence: 99%